The moderating effect of innovation capability on the relationship between corporate entrepreneurship and organizational performance of SMEs in logistics industry in Malaysia / Joehary Sulaiman...[et al.] - Sulaiman, Joehary; Ngah, Rohana; Mohammad Shah, Khairul Anuar; Ab. Kadir, Ahmad Rusydan; Ayob, Arshad (UiTM Cawangan Johor, 2019)
Small and Medium Enterprises (SMEs) has been an integral part to the Malaysia’s economic transformation process. This transformation process is linked with the performance of SMEs. Performance of the SMEs can be viewed from the corporate entrepreneurship (CE) perspectives and the innovation capability (IC) as the moderating factor driving SME performance. In relations to SMEs logistics provider and the significance of corporate entrepreneurship in the SMEs service industry, there are numerous studies which described that corporate entrepreneurship has become a necessary precondition for sustainable business development. Therefore, the focus of this paper is to explore the SMEs performance in Malaysia from the corporate entrepreneurship perspectives and the relevance of innovation capability as a moderator in the organization performance. A research framework will be suggested to be used to explore and test the relationships between CE, IC and OP.